Analisis Kesadaran Guru terhadap RPP dalam Proses Pembelajaran di MI Miftahul Alim Habau - Raihanah Raihanah (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
The background of this research is that there are teachers who rarely use lesson plans in the learning process. Having a priori beliefs about how to teach is good enough that it does not develop the various skills that are important to be mastered and used in class. This study aims to analyze teacher awareness of lesson plans in the learning process at MI Miftahul Alim Habau which includes: analysis of teacher awareness of lesson plans and professionalism, teacher understanding in preparing lesson plans, and implementation of the learning process. This study used a quantitative survey method by collecting data by filling out a questionnaire/questionnaire and using a non-test instrument. The object of research is teachers who teach at MI Miftahul Alim Habau. The results of the study indicate that there is a positive relationship between teacher awareness of lesson plans in the learning process. From the data generated it is also stated that there is a need to increase awareness of using lesson plans in the learning process which is prepared in advance with other learning tools before teaching activities begin. The ability to compile and develop lesson plans is only close to a good correlation value.